2021
DOI: 10.17097/ataunizfd.806072
|View full text |Cite
|
Sign up to set email alerts
|

Atatürk Üniversitesi Ziraat Fakültesi Pilot Süt Fabrikasına Gelen Çiğ Sütlerin Kalitesinin Belirlenmesi

Abstract: Bu araştırmada insan sağlığının korunması ve kaliteli ürünlerin elde edilebilmesine yönelik bir durum tespiti çalışması yapılmıştır. Bu amaçla, Atatürk Üniversitesi Süt Fabrikasına gelen çiğ süt örneklerinden farklı mevsimlerde (yaz, sonbahar, kış ve ilkbahar) 3 faklı üreticiden çiğ süt örnekleri alınmıştır. Bu örneklerde bazı fizikokimyasal analizler (kuru madde, yağ, kül, protein, yoğunluk, asitlik ve pH) ile mikrobiyolojik (somatik hücre sayısı, toplam aerobik mezofilik bakteri (TAMB), maya-küf, koliform gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The protein ratio of raw milk delivered to the pilot milk factory of Atatürk University Faculty of Agriculture ranged between 3.62-3.63 percent, according to a research conducted to determine the quality of raw milk delivered to the pilot milk factory. Furthermore, the protein ratios in the summer and fall seasons are lower than the protein ratios in the spring and winter seasons, according to the results of the same study [48]. The protein ratios of raw milk collected in the summer season are lower than all those collected in other seasons, according to a research analyzing the seasonal effect on the composition of raw milk in Adiyaman [49].…”
Section: 4determination Of Protein Contentmentioning
confidence: 87%
See 1 more Smart Citation
“…The protein ratio of raw milk delivered to the pilot milk factory of Atatürk University Faculty of Agriculture ranged between 3.62-3.63 percent, according to a research conducted to determine the quality of raw milk delivered to the pilot milk factory. Furthermore, the protein ratios in the summer and fall seasons are lower than the protein ratios in the spring and winter seasons, according to the results of the same study [48]. The protein ratios of raw milk collected in the summer season are lower than all those collected in other seasons, according to a research analyzing the seasonal effect on the composition of raw milk in Adiyaman [49].…”
Section: 4determination Of Protein Contentmentioning
confidence: 87%
“…According to this, the milk samples taken from milk collectors in the winter season and the samples taken from farms in the autumn season are both outside the value provided in the relevant proclamation. When comparing studies on the subject, Sengul et al, [64] reported that the density values of raw milk samples fluctuated seasonally in the range of 1.029-1.033 g ml-1 in a study conducted to analyze the quality of raw milk arriving at the Atatürk University Faculty of Agriculture pilot milk factory. The density values of raw milk were measured in the range of 1.023-1.033 g ml-1 in a study conducted to determine some properties of milk supplied from dairy farms and collectors in Adiyaman province [65].…”
Section: 6determination Of Densitymentioning
confidence: 99%